Effects of Th17/Treg cell imbalance on HIV replication in patients with AIDS complicated with tuberculosis - Li, Yanshuang (Exp Ther Med, 2018)
The purpose of this study was to determine the effect of Th17/Treg cell imbalance on HIV replication in patients with AIDS complicated with tuberculosis (TB). We selected 32 patients with AIDS combined with TB infection in our hospital and 30 healthy individual as controls. The Th17/Treg ratio in peripheral blood lymphocytes was detected by flow cytometry. Compared with healthy subjects, Th17 cells first declined in HIV patients with TB, but gradually increased over the course of the disease. Treg showed an increasing trend in HIV patients with TB. The Th17/Treg ratio was significantly altered as the condition gradually deteriorated. ELISA showed that interleukin (IL)-17, IL-6 and IL-10 in patients with HIV complicated with TB were significantly lower than in healthy subjects. The imbalance of Th17/Treg cells can promote HIV virus replication in AIDS patients with TB infection, which can aggravate the condition.